Giant Warty Nevus with Cavernous Angioma Component. Case Presentation - María del Rosario Sánchez Hidalgo; Idalmis Valdés Madrigal; Eduardo Carlos Borges Sánchez (Revista Finlay)
The warty nevus is a benign and congenital hyperplasia of the superficial epidermis and the annexes. It is considered a hamartoma derived from the ectoderm, possibly caused by a chromosomal aberration located on the long arm of chromosome 1.The case of a 3 year-old male patient is presented, with a giant warty nevus with an angioma cavernous component in the occipital region, without other anomalies. Data from documentary sources (such as obstetric card, pediatric card and hospital and outpatient medical records), laboratory and imaging tests, as well as information obtained from the mother's interview, were used to describe the evolution from birth. Issues related to the incidence, locations, age of presentation, clinical and histopathological characteristics, treatment and evolution are discussed, on the bases of a bibliographic search. This report is made due to the low frequency of this pathology at the Paquito González Cueto de Cienfuegos University Pediatric Hospital.